2018
DOI: 10.1146/annurev-ento-031616-035536
|View full text |Cite
|
Sign up to set email alerts
|

Entomological Collections in the Age of Big Data

Abstract: With a million described species and more than half a billion preserved specimens, the large scale of insect collections is unequaled by those of any other group. Advances in genomics, collection digitization, and imaging have begun to more fully harness the power that such large data stores can provide. These new approaches and technologies have transformed how entomological collections are managed and utilized. While genomic research has fundamentally changed the way many specimens are collected and curated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 151 publications
0
46
0
6
Order By: Relevance
“…To facilitate trait‐based research on terrestrial arthropods, there is an abundance of information in the literature and extensive physical and digital collections (Short, Dikow & Moreau, ). The trait‐based approach is also an avenue for overcoming the many taxonomic impediments that have long plagued ecological research on terrestrial arthropods.…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate trait‐based research on terrestrial arthropods, there is an abundance of information in the literature and extensive physical and digital collections (Short, Dikow & Moreau, ). The trait‐based approach is also an avenue for overcoming the many taxonomic impediments that have long plagued ecological research on terrestrial arthropods.…”
Section: Introductionmentioning
confidence: 99%
“…Most existing databases include single view digitisations of pinned specimens (68), while datasets of insect specimens recorded using multiple sensors, 3D models, and databases on living insect specimens are only just emerging (69,70). The latter could be particularly relevant for deep learning models.…”
Section: Digitizing Specimens and Natural History Collectionsmentioning
confidence: 99%
“…The amount and quality of isolated genomic DNA from insect collections depend on a myriad of factors, including killing reagents, method of preservation of specimens in the field, and final voucher storage conditions (Kanda et al, 2015;Short, Dikow & Moreau, 2018). For example, Dillon et al, (1996) (see also Reiss, Schwert & Ashworth, 1995;Gilbert et al, 2007b) found that specimens killed with ethanol yielded significantly higher quantities of high quality DNA compared to other killing/preservation agents such as ethyl acetate vapor, formalin or ethylene glycol.…”
Section: Rule 4: Treat Your Specimens Well To Enhance Their Usementioning
confidence: 99%